ANALISIS SENTIMEN BERDASARKAN KOMENTAR PUBLIK TERHADAP SITUS BELANJA ONLINE PADA FACEBOOK (STUDI KASUS: AKUN FACEBOOK OFFICIAL SHOPEE, LAZADA DAN TOKOPEDIA) - Prasetya, Angga Hadi; Buntoro, Ghulam Asrofi; Astuti, Indah Puji (Universitas Muhammadiyah Ponorogo, 2024)
Online shopping is the process of buying goods and services from merchants that are sold or presented on theinternet. Consumers can visit online shopping sites from home or the office comfortably while sitting in front ofa computer or smartphone. As many as 43% agree that social media is a tool to meet the need for knowledge inthe form of product reviews and forum reviews to help make purchasing decisions. Product reviews and forumreviews are conveyed through comments on social media containing complaints, praise, or views on products orservices from an online shopping site. In Indonesia, there are several e-commerce sites used by consumers. Inthis case, the author only emphasizes the three e-commerce sites, namely Shopee, Tokopedia, and Lazada. Theauthor decided to choose these three sites as research objects because there are many reviews on the three sites,especially on Facebook social media, and to find out the general picture of the perception of Indonesian peoplewho use Facebook towards online shopping sites Lazada, Shopee, and Tokopedia. This analysis provides resultsthat the sentiment of these three online stores tends to get positive sentiment based on comments on Facebooksocial media.